BENTUK DAN MAKNA SIMBOLIK RITUAL ADAT TEING HANG EMPO DALAM MASYARAKAT DESA WAE MOSE KABUPATEN MANGGARAI BARAT (KAJIAN SEMIOTIKA) - Juita, Karolina Elsiana; Jama, Karolus B; Nitbani, Samuel H. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This study aims to analyze the symbolic forms and meanings in the Teing Hang Empo traditional ritual carried out by the people of Wae Mose Village, West Manggarai Regency. This ritual, which means